EFL Students’ English Speaking Motivation during the COVID-19 Pandemic in English Education Major - Ibrahim, Mahanani Ilmi; Kuswardani, Rahayu (Universitas Negeri Surabaya, 2023)
Students’ motivation is one of the challenge for teacher as it is deemed essential to students’ learning activity and outcome. However, maintaining it has become a big issue for teachers during the pandemic. As the pandemic has turned the education system into taking different methods to avoid face-to-face learning, interaction and conversation to practice English for EFL learners have reduced. This present study is aimed to see the English-speaking motivation of Indonesian EFL students in English Education major. 54 EFL students from the English education program at one state university in Surabaya participated in this study. Quantitative method was used in order to collect and analyze the data An online questionnaire was distribute through Google Form in order to collect the data. The participants filled the data based on the 5-point Likert scale. The data was analyzed using SPSS and Microsoft Excel to get accurate result. The result of this study shows most students of English Education major are motivated by their goal of getting a good job (M = 4.64), to be better educated and more confident (M = 4.37), for their success in their program study (M = 4.48) and for professional growth (M = 4.33). The research also found that the participants do not except rewards when they practice their English speaking, although external factors can distract them. The overall result shows that the students of English Education major are both intrinsically and extrinsically motivated. In addition, more students are found to be exclusively intrinsic motivated than extrinsic motivated. Similar tendencies are also found in male and female students in terms of their speaking motivation.